The concept of Sa'ādah in the perspective of Sufism: An analysis of Imam Al-Ghazali's thoughts in Ihya Ulumuddin - Risqiyah, Lailatul; Royanulloh, Royanulloh; Mawardi, Imam (Psikoislamika: Jurnal Psikologi Islam, 2025)
Abstract: This study aims to construct a conceptual model of spiritual happiness (sa'ādah) and analyze the mechanisms for achieving it from the perspective of Imam Al-Ghazali's Sufism. Using qualitative research methods with a content analysis approach, data was collected through purposive selection of key texts in Ihya Ulumuddin that were selected thematically and interpreted using Carol D. Ryff's psychological well-being framework. The Psychological Well-Being (PWB) model emphasizes eudaimonic dimensions, such as self-acceptance, life purpose, and self-development, as its foundation. The results of the study reveal that Al-Ghazali formulated a psychotherapeutic mechanism in which the internalization of the qualities of qanaah (self-satisfaction) and tawadlu (humility) function as interventions to reduce distress caused by greed and ujub, which ultimately leads individuals to a state of ma'rifat as the pinnacle of happiness. These findings have practical implications for Islamic psychology to develop Sufi-based psychotherapy, as well as for modern psychological therapy to integrate spiritual concepts in achieving inner peace. Keywords: Well-being, Happiness; Al-Ghazali; Ihya Ulumuddin; Spirituality. Copyright ©2025. The Authors. Published by Psikoislamika: Jurnal Psikologi dan Psikologi Islam. This is an open access article under the CC BY NO SA. Link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0